REFORMULASI RPP PENERBITAN SERTIFIKAT PENGELOLAAN LAHAN REMPANG GUNA MEWUJUDKAN PENEGAKAN HUKUM DAN PERLINDUNGAN HAK ASASI MANUSIA - Rika Rahayu; Sindi Rahmawati; Zara Azizah Hanan; Farren Mahesa Rangkuti; Nurlaili Rahmawati (ADIL Indonesia Journal, 2024)
The uncertainty of the status of land ownership in Rempang Batam causes conflicts between the government and the local indigenous people. For this reason, this study aims to discuss the reformulation of the RPP for the Issuance of Rempang Land Management Certificates in order to realize Law Enforcement and Human Rights Protection by using normative juridical research methods using a legal approach, concepts and cases. The result of this study is that there are still many Rempang customary law communities whose rights have not been fulfilled in terms of recognition and existence of customary land to the maximum. Therefore, the government’s important role in this case is to issue customary land certificates to ensure customary land rights by MHA Rempang. The factors that caused the chaos between the government and MHA were due to first, the absence of local MHA approval related to the development of Rempang customary land; second, there is an act of Excessive Use Of Force that leads to violence against the local indigenous people; and third, the loss of the right to a sense of security. In resolving the Rempang conflict, it requires patience and cooperation between the government and customary law communities, it is necessary to socialize development projects by the government to local MHAs and make agreements between the two parties so that the rights of Indigenous Peoples remain protected and the Government needs to issue Rempang land management certificates to customary law communities. ABSTRAK Ketidakpastian status kepemilikan lahan Rempang Batam menimbulkan konflik antara pemerintah dengan masyarakat adat setempat. Untuk itu penelitian ini bertujuan untuk membahas tentang reformulasi RPP Penerbitan Sertifikat Pengelolaan Lahan Rempang guna mewujudkan Penegakan Hukum dan Perlindungan Hak Asasi manusia dengan menggunakan metode penelitian yuridis normatif dengan menggunakan pendekatan undang-undang, konsep dan kasus. Hasil penelitian ini adalah Masih banyaknya masyarakat hukum adat Rempang yang belum terpenuhi hak-haknya secara pengakuan dan keberadaan tanah adat secara maksimal. Oleh karena itu, peran penting pemerintah dalam hal ini adalah menerbitkan sertifikat tanah adat guna terjaminnya hak-hak tanah adat oleh MHA Rempang. Adapun faktor yang menyebabkan terjadinya kericuhan antara pihak pemerintah dengan MHA yaitu  karena pertama, tidak adanya persetujuan MHA setempat terkait pembangunan tanah adat Rempang; kedua, terdapat tindakan Excessive Use Of Force berujung kekerasan pada masyarakat adat setempat; serta ketiga, hilangnya hak rasa aman. Dalam penyelesaian konflik Rempang ini membutuhkan kesabaran dan kerja sama antara pemerintah dan masyarakat hukum adat, perlu adanya sosialisasi proyek pembangunan oleh pemerintah kepada MHA setempat dan melakukan kesepakatan antara kedua belah pihak supaya Hak Masyarakat Adat tetap terindungi serta Pemerintah perlu menerbitkan sertifikat pengelolaan lahan rempang kepada masyarakat hukum adat.